Type and direction of laterality vs the choise of the stick of icehockey players - Zadarko, E.; Zadarko-Domaradza, M.; Cybuc, M.; Barabasz, Z. (Slovak Journal of Sport Science, 2017)
Efficient functioning of the nervous system and the high enough level of coordination skills are basic elements enabling athletes to perform complex motor activities which constitute the discipline they practise. The main aim of this work was to establish the relationship between the type and direction of laterality of athletes and the type of the hockey stick used by them during the game. The analysis was performed by means of selected statistical tests. The results revealed a statistically significant correlation between the dominant hand and the types of stick handling of particular players.